Pengaruh Jumlah Baffle Pada Reaktor Koagulasi Hidraulis untuk Menurunkan Parameter TSS dan Kekeruhan - Setyaningtias, Bonita; Aussie Amalia (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The declining quality of river water due to domestic and industrial activities demands effective water treatment technologies. This study aims to evaluate the effect of varying the number of baffles in a hydraulic coagulation reactor on the removal efficiency of Total Suspended Solids (TSS) and turbidity using two types of coagulants: Ferric Chloride (FeCl₃) and Ferrous Sulfate (FeSO₄). The experiment was conducted with baffle variations of 26, 30, 34, 38, and 42, and sedimentation times of 30, 60, and 90 minutes. The results showed that increasing the number of baffles and sedimentation time improved TSS and turbidity removal efficiency up to an optimum point. FeSO₄ achieved the highest TSS removal efficiency of 97% at 42 baffles and 90 minutes of sedimentation, while FeCl₃ demonstrated more stable and high turbidity removal efficiency, reaching up to 97%. Statistical analysis using ANOVA indicated that the type of coagulant, number of baffles, and sedimentation time significantly affected TSS removal, whereas turbidity removal was more influenced by the number of baffles and sedimentation time. These findings highlight the importance of proper hydraulic design in optimizing the coagulation-flocculation process for more efficient water treatment.